A HOLISTIC APPROACH TO ISLAMIC BASIC EDUCATION: SYNTHESIZING THE DEVELOPMENT OF STUDENTS' POTENTIAL FROM INTELLECTUAL, SPIRITUAL AND EMOTIONAL ASPECTS - Siti Fatimah; Sri Sumarni (PIONIR: JURNAL PENDIDIKAN, 2024)
This research aims to explore a holistic approach in Islamic basic education and how this approach can synthesize the development of students' potential from intellectual, spiritual and emotional aspects. The method used is a literature review which includes SINTA accredited articles 1-6 from the last five years. The research results show that curriculum integration that combines intellectual, spiritual and emotional aspects provides significant benefits in increasing students' understanding of the relationship between general knowledge and religious values. Holistic Islamic basic education has also proven effective in developing students' emotional intelligence, which is important for managing emotions, increasing empathy, and building strong character. The role of trained teachers and the support of a supportive learning environment were also identified as important factors in the successful implementation of a holistic approach. Additionally, technology can be used as an effective tool to support holistic learning integration. This study concludes that a holistic approach in Islamic basic education has great potential to create a comprehensive learning environment, which can support students' overall and balanced development. Recommendations for educational practice and further research are also presented to improve the implementation and effectiveness of this approach.Keywords: Holistic Approach, Islamic Basic Education, Potential Development, Intellectual, Spiritual, Emotional